Effective design of one-story metal frame cages - Першаков, В.М.; Коцюбинська, Л.М.; Лоза, І.П.; Місірук, Т.А. (Proceedings of National Aviation University (archive), 2009)
Summarizing and analysis of the constructive decisions of one-storeyed metal frame skeletons of industrial, civil and agricultural buildings under the certificates of authorship and patents of the leading countries for last 20 years is carried out. The most effective designs and direction of their development are revealed.